2018
DOI: 10.22437/ppd.v6i3.5894
|View full text |Cite
|
Sign up to set email alerts
|

Effect of company size, liquidity and operational efficiency on bank profitability with problem credit risk as a moderating variable at commercial banks that are listed on the Indonesia Stock Exchange

Abstract: This study aims to measure and analyze the influence of company size, liquidity and operational efficiency on bank profitability with problem credit risk as a moderating variable at commercial banks that are listed on the Indonesia stock exchange. The unit of analysis in this study is 30 commercial banks listed on the official website of Bank Indonesia for the period 2012-2016. The type of data used is panel data with data analysis using purposive sampling method. The results of the study found that the size o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 3 publications
1
12
0
1
Order By: Relevance
“…Meanwhile, the regression results of operational efficiency on the ROA and ROE are consistent with the findings of [57,68,69,70] that found a significant negative effects of the operational efficiency on profitability such as ROA and ROE of the firms. Thus, high operational efficiency by reducing cost in Islamic banks would lead to enhance the profitability of the banks.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Meanwhile, the regression results of operational efficiency on the ROA and ROE are consistent with the findings of [57,68,69,70] that found a significant negative effects of the operational efficiency on profitability such as ROA and ROE of the firms. Thus, high operational efficiency by reducing cost in Islamic banks would lead to enhance the profitability of the banks.…”
Section: Discussionsupporting
confidence: 90%
“…Regarding banking industries, an operational efficiency ratio implied the bank capacity to optimise operating expense management and profitability. Notably, past research affirmed the operating efficiency-bank profitability correlation [14,69,70]. The studies demonstrated that organisations implementing minimal cost operations potentially improved the bank profitability represented by ROA ratio.…”
Section: Operational Efficiencymentioning
confidence: 79%
“…The capital aspect, which is the first problem MSMEs face, can be a solution (Adam, Safitri & Wahyudi, 2018). For Islamic Microfinance Institutions that apply sharia principles and financial institutions, especially micro Waqf banks, this policy encourages fund providers to open their fund distribution taps more widely (Wowoho, 2014).…”
Section: Policy Impacts On Micro Waqf Banks In Indonesiamentioning
confidence: 99%
“…The most important factor to keep banks healthy is to maintain the trust of prospective bank users Ajeng Tita Nawangsari them selves. This is because the main capital of banks is public trust (Adam, et al 2018). There are several alternatives to measure Islamic banks' performance besides using profitability indicators and using various financial indicators with Islamic perspective aspects (Nugroho, et al 2021).…”
Section: Introductionmentioning
confidence: 99%